Updated National Multicenter Registry on Procedural Safety of Catheter Ablation for Atrial Fibrillation. (25th June 2013) - BERTAGLIA, EMANUELE; STABILE, GIUSEPPE; PAPPONE, ALESSIA; THEMISTOCLAKIS, SAKIS; TONDO, CLAUDIO; SANCTIS, VALERIO DE; SOLDATI, EZIO; TRITTO, MASSIMO; SOLIMENE, FRANCESCO; GRIMALDI, MASSIMO; ZOPPO, FRANCO; PANDOZI, CLAUDIO; et al.
Safety of Catheter Ablation for Atrial Fibrillation Introduction Despite catheter ablation (CA) becoming an accepted treatment option for symptomatic, drug‐resistant atrial fibrillation (AF), safety of this procedure continues to be cause for concern. Aim of the present multicenter registry was to assess the incidence of early CA complications and detect their predictors in a contemporary, unselected AF population Methods and Results From January 1, 2011 to December 31, 2011, data from 2, 323 consecutive patients who underwent CA (median age 60 [52–67]; 72.3% male) for AF in 29 Italian centers were collected. All major complications occurring to the patient from admission to 30th postprocedural day were recorded. No procedure‐related death was observed. Major complications occurred in 94 patients (4.0%): 50 patients (2.2%) suffered vascular access complications; 12 patients (0.5%) developed cardiac tamponade; 14 patients (0.6%) presented with pericarditis; 5 patients (0.2%) had transient ischemic attack; 4 patients had stroke; 3 patients (0.1%) had phrenic nerve paralysis; 3 patients (0.1%) had hemothorax. Other isolated but serious adverse events were documented in 3 patients (0.1%). Female gender (OR 2.643; 95% CI 1.686–4.143; P < 0.0001) and longer procedural duration (OR 2.195; 95% CI 1.388–3.473; P < 0.001) independently predicted a higher risk of complications. Conclusion Major complications occurred in 4.0% of the CA procedures for AF, with vascular access complications being the most frequent events.